EVALUASI REAKTIFITAS KATALIS NIMO DALAM PROSES PENCAIRAN BATUBARA BANKO SELATAN DAN AUSTRALIAN LOY YANG - Hartiniati, Hartiniati (Badan Pengkajian dan Penerapan Teknologi, 2008)
Indonesia South Banko (BS) and Australian Loy Yang (LY) were liquefied usingtwo hydrogenation catalysts, Ni/Mo and Co/Mo at mild condition (400oC, 6MPa(H2 cold)). The study shows that the use of Ni/Mo in hydrogenation for both BSand LY coals gives a higher total conversion, asphaltene and OGW (oil-gaswater)yields than that of Co/Mo. The use of Ni/Mo for LY coal hydrogenationgives higher total coanversion and asphaltene yield than SB coal. This suggeststhat SB has more condensed structure than LY coal. However, the amount of oilyield is similar for both coals. Furthermore, the use of Co/Mo for both coals alsogives almost equal result in total conversion, asphaltene and OGW yields.Addition of sulphur (as CS2) enhances the total conversion and OGW yield forboth catalysts Ni/Mo and Co/Mo. Sulphur addition on Ni/Mo treated coal did notimprove the asphaltene yield, but converted it into lower molecular weight.Adding sulphur could also improve total conversion for Co/Mo treated coal similarto Ni/Mo/CS2 treated coal. Increasing reaction time also improves the totalconversion, asphaltene and OGW yield. The reactivitiy of BS and LY in this studyis also dependent on their behaviour or characteristic, such the environment ofoxygen content in the macro structure of the coal.Kata kunci: south banko coal, australian loy yang coal, ni/mo catalyst, co/mocatalyst, asphaltene, coal liquefaction